Russian civil-military relations - Brannon, Robert (Robert Burl) 1950- (Military strategy and operational art, 2009)
Deriving in part from its Soviet past, Russia's military doctrine represents more than just a road map of how to fight the nation's wars; it also specifies threats to national interests, in this case the United States, NATO and international terrorism. Against this background, Robert Brannon demonstrates that the military's influence may reveal as much about politics as it does the military.